An Analysis of Offal Meat Consumption Pattern: A case of Srinagar District in Jammu and Kashmir : 10.5958/2581-6616.2020.00011.0 - Ayman, Niha; Hamdani, S. A.; Fayaz, Aaliya; Akand, A. H.; Hai, Abdul; Thahaby, Namera (Journal of Meat Science, 2021)
Offals are entrails and internal organs of animals used as food. Its consumption has a tremendous regional impact that ranges from local  to global where a range of factors like social, economic and cultural determine the consumer behaviour towards offal meat consumption.  The present study was purposively carried out in Srinagar city of Kashmir region in order to understand the consumption behavior  towards offals among the consumers in this district. The major findings of the study reveal that majority of the households were Muslims, living in nuclear families with most of them having business as their main occupation and average annual income of Rs.409665.30.  Among the different types of offals, red offals was the most preferred one where habituation towards its consumption turned out to be  major reason for such selective preference. Dark offals were the least preferred type of offal meat among the lot and grey offals were also  consumed by only half portion (53.06 %) of population. Taboo associated with the consumption of these two said offals was hindering  their uptake. With regard to consumption of offals, an average monthly consumption turned out to be 0.74 kg; 1.06 kg and 0.49 kg for  grey, dark and red offals per household respectively and average monthly expenditure of Rs. 184.49; 251.05 and 122.25 was spent on  grey, dark and red offals respectively among households which clearly indicates that the demand of overall offal meat was very low in  Srinagar city. So, there is need with regard to our authorities, leaders and municipalities to enlighten people about the nutritional benefits  of offal meat consumption.
Keywords: Consumption pattern; Dark offals; Grey offals; Red offals; Srinagar city